Adsorption and magnetic solid-phase extraction of NSAIDs from pharmaceutical wastewater using magnetic carbon nanotubes: Effect of sorbent dimensions, magnetite loading and competitive adsorption study - El-Sheikh, Amjad H.; Qawariq, Rania F.; Abdelghani, Jafar I. (Environmental technology & innovation, 2019)
Magnetic carbon nanotubes (MCNT) of different dimensions and different magnetite-to-carbon nanotube (Mag:CNT) ratios were prepared and characterized for magnetic solid phase extraction (MSPE) of some non-steroidal anti-inflammatory drugs (NSAIDs) (ketoprofen (KET), diclofenac sodium (DIC) and ibuprofen (IBU)) from water prior to their HPLC determination. The results revealed that the best mixing ratio of (Mag:CNT) was at (1:1) ratio; long CNT was better than short CNT; the best external diameter was 60-100 nm. This sorbent was labelled as L-MCNT60-100nm(1:1). The optimum MSPE-HPLC method was as follows: 150 mg of L-MCNT60-100nm(1:1) sorbent was added to 50 mL solution containing KET, DIC and IBU at pH 5. The solution was shaken for 30 min and the sorbent was separated from the solution using an external magnet. The adsorbed analytes were eluted using 5 mL of 10% ammonia in methanol and the eluent was then injected into HPLC instrument. Figures of merit were estimated to be as follows (KET, DIC and IBU, respectively): detection limits: 0.4, 0.5, 0.5 μg L−1; sensitivity: 3.13, 3.40, 1.46 L mg−1; %RSD range: [2.6–7.2], [2.2–5.1], [2.7–6.4] %; bias range (%): [(-26.8)–(14.0)], [(-7.4)–(17.0)], [(-8.4)–(17.8)]%. Application on tap water and pharmaceutical wastewater gave spiked recovery as follows: Tap water: KET: 103.7%(±5.4); DIC: 110.3%(±5.3); IBU: 70.1%(±6.5); Pharmaceutical wastewater: KET: 58.8%(±7.2); DIC: 48.9%(±5.9); IBU: 100.5%(±8.2). Adsorption studies were conducted to measure the adsorption capacity of the adsorbents where the effect of MCNT dimensions, magnetite loading and competitive adsorption were investigated.